356 Baseline PD-L1 expression and tumor immune infiltration is associated with clinical response in patients with r/r DLBCL treated with DPX-Survivac, low-dose cyclophosphamide and pembrolizumab. (9th November 2020) - Berinstein, Neil; Bence-Bruckler, Isabelle; Forward, Nick; Laneuville, Pierre; Mangel, Joy; Stewart, Douglas; Amitai, Irina; Klein, Gail; Pennell, Nancy; Rashedi, Iran; Roos, Kim; Bramhecha, Yogesh; et al.
Abstract : Background: Treatment of recurrent/refractory (r/r) DLBCL remains an unmet clinical need, and new effective and well-tolerated treatments are required. DPX-Survivac is a unique T cell activation therapy that targets survivin-expressing tumor cells and has shown anti-tumor activity in clinical trials. This trial is evaluating a novel immunotherapy combination with DPX-Survivac, intermittent low dose CPA and pembrolizumab. Methods: 'SPiReL' is a Phase 2 non-randomized, open label, efficacy and safety study of a novel immunotherapy combination with DPX-Survivac (a unique T cell activation therapy that targets survivin-expressing tumor cells), intermittent low dose CPA and pembrolizumab, treatment regimen as described in figure 1 . Subjects with r/r incurable DLBCL and survivin expression are eligible for participation. This study was approved by the Ontario Cancer Research Ethics Board, approval number 0981.ORR is assessed by modified Cheson criteria. For translational analyses, baseline and on-treatment PBMCs, along with tumor biopsy samples are collected from each subject. Survivin-specific systemic T cell responses are assessed using IFNγ-ELISPOT assay and tumour immune-infiltrate profile by multiplex-IHC. Results: Twenty-two subjects have been enrolled to date, 19 are included in the intent to treat (ITT) population and 11 subjects are evaluable in the per protocol (PP) population. In the PP, the ORR is 63.6% including 3 CRs (27.3%), 4 PRs (36.4%) and the DCR is 81.8% (9/11). In the ITT, the ORR is 35% (7/19), and DCR is 52.0% (10/19). Preliminary results show that non-GCB subjects had a higher proportion of clinical response (4/8, 50%), compared to 3/10 (30%) in GCB subjects.DPX-Survivac-induced T cell responses were observed in 8/19 subjects (42.1%) including 6 subjects with clinical response (PR, CR), one SD and one PD. Multiplex-IHC analyses demonstrated baseline tumor PD-L1 expression in 6/7 subjects with a clinical response (85.7%, p<0.05). Similarly, subjects with higher baseline CD4+ and CD8+ T cell infiltration demonstrated a trend towards clinical response (table 1 ). Conclusions: DPX-Survivac, intermittent low-dose CPA and pembrolizumab is generally well tolerated and can induce clinical responses in subjects with r/r DLBCL (7/11, 63.6% of evaluable subjects), including subjects with both non-GCB and GCB subtypes. Pre-treatment biopsies of clinical responders were characterized by higher baseline tumor PD-L1 expression and CD4 and CD8 infiltration. Extending this exploratory data in a larger cohort may define a r/r DLBCL patient population with a higher likelihood to respond to this novel combination immunotherapy. Trial Registration: NCT03349450 Ethics Approval: This study was approved by the Ontario Cancer Research Ethics Board, approval number 0981.